Revisiting the Medical Management of Parkinson's Disease: Levodopa versus Dopamine Agonist - Zhang, Jinglin (Curr Neuropharmacol, 2016)
The optimal treatment strategy for Parkinson's disease has been debated for decades. The introduction of levodopa (LD) treatment is frequently delayed because of theoretical concerns about its toxicity or the risk of drug-induced motor complications. These concerns have resulted in “LD phobia” with clinicians selecting dopamine agonist (DA) over LD as initial therapy. More recently, a shift in the treatment approach towards initial LD use appears to be occurring. It is therefore necessary to review current evidence for the use of LD and DA. This review discusses the medical management of Parkinson's disease with regards to the use of LD versus DA. Pendulum swings in treatment strategies between LD-first and DA-first therapies should be avoided. A balanced perspective is needed as there is a place for both drugs in the management of PD.